Clustering of COPD patients and their response to pulmonary rehabilitation. (July 2022) - Al Chikhanie, Yara; Bailly, Sébastien; Amroussa, Ines; Veale, Daniel; Hérengt, Frédéric; Verges, Samuel
Abstract: Background and objective: Pulmonary rehabilitation (PR) is fundamental in the management of chronic obstructive pulmonary disease (COPD). COPD patients show a large clinical heterogeneity that may influence their response to PR. Identification of homogeneous clusters of patients who may or may not respond to PR is important to personalize patient care. This study aimed at identifying distinct clinical phenotypes of COPD patients and assessing their respective 6-min walking distance (6MWD) response to in-patient PR. Methods: This is a cohort-based analysis of COPD patients admitted to a PR center between January 2012 and December 2017. Pre-PR patients' characteristics, lung function and 6-min walking test parameters were introduced in a hierarchical ascending clustering approach to identify distinct clusters. Results: Out of 835 patients, 4 distinctive clusters were identified. The most likely to show clinically significant 6MWD improvement post-PR (responders) were cluster 1 (younger men, GOLD I-II, average walkers, obese; non-response rate: 16%), cluster 2 (older women, GOLD II-III, slow walkers; 18%), and cluster 3 (older men, GOLD II-III, dyspneic, slow walkers; 11%). The most likely to be non-responders were cluster 4 (older men, GOLD III-IV, dyspneic, very slow walkers, oxygen-dependent; 26%). Conclusion: Our data identified homogeneous patient clusters representing clinically relevant subgroups of COPD patients regarding their 6MWD response to PR. Clusters having the largest probability of being non-responders were older, more severe, with severe oxygen desaturation and dyspnea, limited 6MWD and requiring long-term oxygen therapy. These results may improve patient phenotyping in clinical practice and allow individualization of therapy.